NILAI KEPEMIMPINAN DAN FILSAFAT SENI DALAM KEKAWIN NITI SASTRA - Heppyana, Ni Putu Ayu (Widya Katambung, 2025)
Hinduism is a essence that cannot be separated from artistic life, culture and social leadership. An art will create Hinduism into a beautiful essence and have meaning which can then be felt deeply by Hindus. Kakawin Niti Sastra is evidence of literary works that exist to serve as a guide for Hindus in realizing artistic values ​​and leadership values. Kakawin NitiSastra, as a guide for leaders in carrying out their activities wisely, with compassion, courage and adhering to the truth, all of which are ideological values ​​that can support the continuity of good leadership in society. By understanding and applying these values, a leader is expected to be able to protect and improve the welfare of his community. Art, as a cultural and spiritual expression, has a depth of meaning that is closely related to religious beliefs and practices, especially in the Hindu context, where art is considered a means of conveying a sense of devotion to God. Keywords: Phylosophy Art, Social Leadership, Kakawin NitiSastra